(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper deals with dynamical analysis of a food-web including three logistically growing interaction species, prey, intermediate predators and apex predators. The intermediate predator species predate the prey species according to the Holling type-II functional response, while the apex predator species predate both prey species and intermediate predator species according to extended Holling type II functional response for two prey species. Firstly, the criteria that make the model permanent are determined and then all biologically possible steady states are explored, and their local stability as well as global stability is analyzed based on the sample parameters. The occurrence of Hopf-bifurcation of thee model near all steady states, are discussed. Finally, with the help of MATLAB program, it is performed numerical simulations to support the evidence of our analytical results.